Controlled Microstructural Architectures Based on Smart Fabrication Strategies. (16th April 2019) - Ding, Haibo; Zhang, Qiming; Gu, Hongcheng; Liu, Xiaojiang; Sun, Litao; Gu, Min; Gu, Zhongze
Abstract: Controlled microstructural architectures—artificially designed microstructures and nanostructures with controlled properties—have been extensively used in scientific research and practical applications. Advanced fabrication strategies are always desired to satisfy the increasing demands for specific architecture designs. This review highlights the recent progress in bottom‐up methods based on self‐assembly and top‐down methods by using two‐photon polymerization. As an emerging additive manufacturing technology, two‐photon polymerization has shown the enormous potential of being a general fabrication method for controlled microstructural architectures due to its unique advantage in direct laser writing of 3D microstructures with high resolution. This review also covers some remaining challenges for controlled microstructural architectures, along with future outlooks. Abstract : Advanced fabrication strategies are desired to generate artificially designed microstructures and nanostructures with controlled properties. This review summarizes the representative models of these controlled microstructural architectures (CMA) and highlights the recent progress in self‐assembly and two‐photon polymerization (TPP). Above all, TPP has shown an enormous potential for being a general fabrication method for CMA.